A systematic review of event-level measures of risk-taking behaviors and harms during alcohol intoxication. (December 2019) - Brooks, Michael; Nguyen, Rebecca; Bruno, Raimondo; Peacock, Amy
Abstract: Alcohol intoxication is associated with transient increases in risk-taking behaviors which can lead to harm. Certain assessment and intervention evaluation approaches require measurement of risk behaviors and associated harms at the event-level (i.e., within a single drinking session). This systematic review aimed to identify measures solely assessing risk-taking behaviors and harms while intoxicated and identify evidence of their reliability and validity. EMBASE, Medline, PsycINFO, and PsycTESTs were searched for articles published between 1997 and 2019. Articles were selected based on use of a scale with one or more items measuring risk-taking behaviors and harms (to the individual or others around them) occurring while intoxicated. Additional searches were run to identify studies reporting estimates of reliability and validity for identified measures. Nineteen measures were identified containing at least one relevant item. Most measures indexed both acute and chronic risk behaviors and consequences, mainly with the intent of screening for established patterns of problematic use. No individual measure was identified exclusively quantifying risk-taking behavior and harms which had occurred within a drinking session (with the exception of one scale measuring tendency to engage in risk behaviors), yet three measures had a subscale meeting this criterion. These measures demonstrated good validity and reliability. This gap represents an opportunity for scale development, designed for use in ecological momentary assessment and evaluation of structural interventions targeting risk behaviors and harms whilst intoxicated. Highlights: Systematic review of scales measuring behaviors and consequences while intoxicated. Nineteen scales were identified with at least one relevant item. No one scale met criteria; three measures with relevant subscales were identified. Opportunity to develop measures for ecological momentary assessment whilst intoxicated.